The Policy Alignment of the British False Memory Society and the British Psychological Society. Issue 2 (15th March 2022) - Conway, Ashley; Pilgrim, David
ABSTRACT: This paper describes the alignment between the goals of the British False Memory Society (BFMS) and a group of sympathetic academics within the British Psychological Society (BPS). Since the 1990s, the policy formation process of the BPS has excluded critical colleagues concerned with child protection and the demonstration of the link between childhood adversity and adult mental health problems. Those involved in the nexus between the BPS and BFMS have focused singularly on the experimental evidence for false-positive outcomes and have systematically excluded a consideration of false negatives. We describe how this biased policy development emerged and was maintained. We discuss this skewed policy formation with reference to social network formation in professional life, as well as the wider context of child abuse in society.